Apego emocional y su incidencia en la autoestima de una adolescente de 16 años de la Unidad Educativa Particular Padre Daniel Diez García en el cantón Simón Bolívar - Yance Moncerrate, Melissa Michell (2023)
The present case study was conducted with the purpose of establishing the effect of attachment and self-esteem problems in a 16-year-old adolescent girl from the Unidad Educativa Particular Padre Daniel Diez García of the Simón Bolívar canton, with the objective of analyzing the effect of attachment on the self-esteem of the adolescent girl and modifying the symptoms that cause clinically significant discomfort and the training of social skills to improve her quality of life. For which information gathering techniques were used, such as psychoeducation, observation guide, use and filling out of the clinical history, use of psychometric tests, through a semi-structured interview, by means of which separation anxiety disorder was established as a diagnosis, so that her low self-esteem, emotional attachment, difficulties in establishing healthy emotional boundaries, Taking as a guideline the criteria provided by the DSM-V Manual and the ICD 10 Manual, a psychotherapeutic intervention scheme was implemented with the child, taking into consideration that the evolution of her disorder is directly related to the work and constancy with which the cognitive behavioral techniques are carried out at home and in the educational institution she attends.